KONSEP PENDIDIKAN DALAM DONGENG ANAK TRADISIONAL ACEH AMAT RHYANG MAYANG DAN PUTROE GUMBAK MEUH - RR. Siti Murtiningsih (Jurnal Filsafat "WISDOM", 2010)
AbstractTraditional folklores for Aceh people have significant roles in the education field as tools in transfering knowledge and cultural values. This paper researches two of the Aceh folklores, Amat Rhyang Mayang and Putroe Gumbak Meuh. The two folklores are full of educational values. The educational values are the concepts of education which mainly base on essentialism and perennialism school of educationKeywords: education, essentialism, perennialism, traditional folkloreof Aceh, Amat Rhyang Mayang, Putroe GumbakMeuh.